2022
DOI: 10.1186/s12885-022-09778-9
|View full text |Cite
|
Sign up to set email alerts
|

Pre-diagnostic C-reactive protein concentrations, CRP genetic variation and mortality among individuals with colorectal cancer in Western European populations

Abstract: Background The role of elevated pre-diagnostic C-reactive protein (CRP) concentrations on mortality in individuals with colorectal cancer (CRC) remains unclear. Methods We investigated the association between pre-diagnostic high-sensitivity CRP concentrations and CRP genetic variation associated with circulating CRP and CRC-specific and all-cause mortality based on data from 1,235 individuals with CRC within the European Prospective Investigation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…To date, the associations between FV intake and in ammatory biomarkers levels including CRP have been suggested [16,44]. Besides, studies also consistently reported that CRP level was associated with premature death from allcause, cardiovascular and cancer [45][46][47][48]. Our ndings provided quantitative evidence supporting the plausible hypothesis that fruit and vegetables intake plays a key role in premature death through reducing in ammatory biomarker CRP level.…”
Section: Discussionsupporting
confidence: 76%
“…To date, the associations between FV intake and in ammatory biomarkers levels including CRP have been suggested [16,44]. Besides, studies also consistently reported that CRP level was associated with premature death from allcause, cardiovascular and cancer [45][46][47][48]. Our ndings provided quantitative evidence supporting the plausible hypothesis that fruit and vegetables intake plays a key role in premature death through reducing in ammatory biomarker CRP level.…”
Section: Discussionsupporting
confidence: 76%
“…High resistin levels in the “steady‐state” conditions could be caused by CLGSI, which many conditions may have triggered. Under CLGSI, C‐reactive protein (CRP), an inflammatory marker, was not significantly associated with CRC mortality, as previously reported 34 . Of the conditions that trigger CLGSI, obesity is typical, as inflammation is initially induced in white adipose tissue and extends to other tissues and circulation, resulting in CLGSI 35 .…”
Section: Discussionmentioning
confidence: 54%
“…Under CLGSI, C-reactive protein (CRP), an inflammatory marker, was not significantly associated with CRC mortality, as previously reported. 34 Of the conditions that trigger CLGSI, obesity is typical, as inflammation is initially induced in white adipose tissue and extends to other tissues and circulation, resulting in CLGSI. 35 Pre-diagnostic obesity was reported as a significant factor in the risk of death in patients with non-metastatic CRC.…”
Section: Measurements Of Resistin Concentrations After Crc Diagnosismentioning
confidence: 99%
“…C-reactive protein (CRP) levels are typically thought of as a biomarker for inflammatory response and not as a pathogenetic factor, although inherited CRP variants have been associated with, and thus possibly a modifying factor in some infections [ 22 , 23 ] response to vaccination, [ 26 ] as well as other conditions such as cancer [ 44 , 45 ] and pre-eclampsia [ 46 , 47 ]. For this reason, we selected 4 available variants related to CRP expression for our analysis.…”
Section: Methodsmentioning
confidence: 99%